Sanctity and quality as the conceptual basis of the value of life doctrine in the bioethical discourse - Олександр Горбань; Руслана Мартич (Cхід, 2024)
The article offers a study of the bioethical discourse regarding the value of life through the prism of conceptualizing the main approaches to the study of this phenomenon. It is noted that with all the diversity of approaches that demonstrate a wide range of views on the value of life, the modern bioethical discourse com-bines the ideas of scientific research, the dogmatics of religious doctrines and the basic principles of moral imperatives, which are interpreted in a civilized soci-ety in the context of medico-biological problems of life preservation and repro-duction, as well as determining its value. This combination is far from being ec-lectic. It synthesizes the main achievements of scientific, religious and ethical thought and extrapolates them to the problem of human life, which is a unique phenomenon that should be separated into a specific system of moral norms and imperatives of human activity. The article notes that in modern conditions the bioethical discourse is concentrated around the axiological paradigm in the study of living beings. All the diversity of viewpoints is proposed to be grouped into two main approaches: the ethics of the sacredness (sanctity) of life and the the quality of life ethics. The conceptualization of these two main approaches permits to consider all the diversity of views on the value of life in the context of bioethi-cal discourse as a systematized set of views, which contributes to the creation of an appropriate scientific research situation and will contribute to the deepening of scientific studies on the specified subject.